2015
DOI: 10.1007/s11661-015-2956-7
|View full text |Cite
|
Sign up to set email alerts
|

Forge Welding of Magnesium Alloy to Aluminum Alloy Using a Cu, Ni, or Ti Interlayer

Abstract: HIDEKI YAMAGISHI, JUNJI SUMIOKA, SHIGEKI KAKIUCHI, SHOGO TOMIDA, KOUICHI TAKEDA, and KOUICHI SHIMAZAKI The forge-welding process was examined to develop a high-strength bonding application of magnesium (Mg) alloy to aluminum (Al) alloy under high-productivity conditions. The effect of the insert material on the tensile strength of the joints, under various preheat temperatures and pressures, was investigated by analyzing the reaction layers of the bonded interface. The tensile strengths resulting from direct b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In a basic study for the development of next-generation spot-joining equipment, it was demonstrated that the forge-welding method [20][21][22] can be applied to Fe 9 Al spot welding. [23,24] Forge welding is a method whereby a contaminated layer (e.g., an oxide at the interface) is removed by plastic flow; diffusion bonding occurs on the new surface within a short period of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a basic study for the development of next-generation spot-joining equipment, it was demonstrated that the forge-welding method [20][21][22] can be applied to Fe 9 Al spot welding. [23,24] Forge welding is a method whereby a contaminated layer (e.g., an oxide at the interface) is removed by plastic flow; diffusion bonding occurs on the new surface within a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a quality assurance advantage of this joining method, the joint strength could be guaranteed at all points, depending on the thickness of the joint or the amount of punch insertion. There is a wide range of applicable material combinations, such as Fe 9 Al and other dissimilar material combinations described thus far [20][21][22] ; these combinations include Al 9 copper (Cu), Al 9 titanium (Ti), Al 9 nickel (Ni), Cu 9 magnesium (Mg), Ti 9 Mg, and Ni 9 Mg. Furthermore, this method can use Al 9 Al joints, for which ordinary resistance spot-welding is difficult due to the high current required by the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…For other welding processes, adding metal interlayer is an important way of reducing the formation of IMCs, such as resistance spot welding with a Zn coated steel interlayer [22] or Zn interlayer [23], forge welding with a Cu, Ni, or Ti interlayer [24], laser welding with a Ti interlayer [25], diffusion welding with a Zn interlayer [26], pre-roll-assisted A-TIG welding with a Zn interlayer [27] and ultrasonic spot welding with a Sn interlayer [28]. However, for Mg–Al FSSW, welding temperature is not high, so the insertion of metal layer with low melting point between the Mg and Al sheets is a more promising way of mitigating the formation of undesirable IMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 12 added a Cu layer to the Al-Zn-Mg-Cu FSW lap joints and found a significant positive relationship between the Cu layer and the joint strength. Although Wang et al 13 and Yamagishi's team 14 used Cu interlayer for butt and lap welding, the former mainly studies the improvement of the joint strength by pulse current. At the same time, the latter had a Cu layer lap joint strength of 100 MPa, which lacks further improvement.…”
Section: Introductionmentioning
confidence: 99%